2016
DOI: 10.1155/2016/8506214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subsequent Dilute Acid and Enzymatic Hydrolysis on Reducing Sugar Production from Sugarcane Bagasse and Spent Citronella Biomass

Abstract: This work was aimed at investigating the effect of process parameters on dilute acid pretreatment and enzymatic hydrolysis of spent citronella biomass (after citronella oil extraction) and sugarcane bagasse on total reducing sugar (TRS) yield. In acid pretreatment, the parameters studied were acid concentration, temperature, and time. At the optimized condition (0.1 M H2SO4, 120°C, and 120 min), maximum TRS obtained was 452.27 mg·g−1and 487.50 mg·g−1for bagasse and citronella, respectively. Enzymatic hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In our experiments, saccharification rates were significantly higher after 72 h than after 24 and 48 h. Similarly with previous study [39] pretreated rice straw with ionic liquid showed that saccharification times of 24 and 72 h produced glucose yields of 75.4% and 90.9%, re- According to previous researcher [23] total reducing sugar (TRS) yields from hydrolysis of sugarcane bagasse and spent citronella biomasses increased with acid concentrations and reaction times. The highest TRS yield from citronella and bagasse was achieved after 48 h at 50 °C with 10 FPU of cellulase.…”
Section: Effects Of Dilute Acid and Alkaline Concentrations On Sacchasupporting
confidence: 89%
See 3 more Smart Citations
“…In our experiments, saccharification rates were significantly higher after 72 h than after 24 and 48 h. Similarly with previous study [39] pretreated rice straw with ionic liquid showed that saccharification times of 24 and 72 h produced glucose yields of 75.4% and 90.9%, re- According to previous researcher [23] total reducing sugar (TRS) yields from hydrolysis of sugarcane bagasse and spent citronella biomasses increased with acid concentrations and reaction times. The highest TRS yield from citronella and bagasse was achieved after 48 h at 50 °C with 10 FPU of cellulase.…”
Section: Effects Of Dilute Acid and Alkaline Concentrations On Sacchasupporting
confidence: 89%
“…Residues were removed from solutions using filter paper on a vacuum filtration unit and were washed with distilled water to obtain neutral pH. Pretreated substrates were washed with water to reduce inhibitory product concentrations [23]. Residues were then dried until a constant weight was achieved and were used for the subsequent processing steps.…”
Section: Pretreatment Of Palm Tree Trunk Wastementioning
confidence: 99%
See 2 more Smart Citations
“…Several different acids used in pretreatments of SCB, including dilute sulfuric acid [29][30][31][32][33][34][35], dilute hydrochloric acid [36], dilute phosphoric acid [32,37], and dilute nitric acid [38], have been reported. High hydrolysis yields have been obtained when lignocellulosic biomass was pretreated with dilute sulfuric acid compared with hydrochloric, phosphoric, and nitric acid [22].…”
Section: Country Bioethanol Production (Million Gallon)mentioning
confidence: 99%